Phytosomes as a Plausible Nano-Delivery System for Enhanced Oral Bioavailability and Improved Hepatoprotective Activity of Silymarin - Ravi Gundadka Shriram; Afrasim Moin; Hadil Faris Alotaibi; El-Sayed Khafagy; Ahmed Al Saqr; Amr Selim Abu Lila; Rompicherla Narayana Charyulu (MDPI AG, 2022)
Silymarin, a phyto-constituent derived from the plant Silybum marianum, has been widely acknowledged for its hepatoprotective activities. Nevertheless, its clinical utility is adversely hampered by its poor water-solubility and its limited oral bioavailability. The aim of this study was to investigate the efficacy of phospholipid-based phytosomes for enhancing the oral bioavailability of silymarin. The phytosomes were prepared using the solvent evaporation technique and were optimized using a full factorial design. The optimized silymarin phytosomal formulation was then characterized for particle size, surface morphology, aqueous solubility, and in vitro drug release. Furthermore, in vivo antioxidant activity, hepatoprotective activity and oral bioavailability of the optimized formula were investigated in a rat model. The prepared silymarin phytosomes were discrete particles with a porous, nearly smooth surface and were 218.4 ± 2.54 nm in diameter. In addition, the optimized silymarin phytosomal formulation showed a significant improvement in aqueous solubility (~360 µg/mL) compared to pure silymarin and manifested a higher rate and extent of silymarin release from the optimized formula in dissolution studies. The in vivo assessment studies revealed that the optimized silymarin phytosomal formulation efficiently exerted a hepatoprotective effect in a CCl4-induced hepatotoxicity rat model via restoring the normal levels of antioxidant enzymes and ameliorating cellular abnormalities caused by CCl4-intoxication. Most notably, as compared to pure silymarin, the optimized silymarin phytosomal formulation significantly improved silymarin oral bioavailability, as indicated by a 6-fold increase in the systemic bioavailability. Collectively, phytosomes might represent a plausible phospholipid-based nanocarrier for improving the oral bioavailability of phyto-constituents with poor aqueous solubility.